2018
DOI: 10.1094/pdis-01-18-0060-re
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Disease of Big-Leaf Mahogany Caused by TwoFusariumSpecies in Mexico

Abstract: Big-leaf mahogany (Swietenia macrophylla) is valued for its high-quality wood and use in urban landscapes in Mexico. During surveys of mango-producing areas in the central western region of Mexico, symptoms of malformation, the most important disease of mango in the area, were observed on big-leaf mahogany trees. The objectives of this research were to describe this new disease and determine its cause. Symptoms on big-leaf mahogany at four sites in Michoacán, Mexico resembled those of the vegetative phase of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 45 publications
0
7
0
2
Order By: Relevance
“…The 94 fungal isolates were grown in dextrose potato broth (PDB) for 7 days, then the mycelium was compacted, dried, and ground with liquid nitrogen for DNA extraction using the CTAB protocol [11]. The DNA extracted was used to amplify the partial region of the TEF1 gene by PCR and the PCR products were resolved by electrophoresis in 1.5% agarose gel, later purified with Promega's Wizard SV Gel and PCR Clean-Up System kit and they ordered sequencing to the Potosí Institute for Scientific and Technological Research (San Luis Potosí, Mexico).…”
Section: Molecular Characterization Of Fungal Isolatesmentioning
confidence: 99%
“…The 94 fungal isolates were grown in dextrose potato broth (PDB) for 7 days, then the mycelium was compacted, dried, and ground with liquid nitrogen for DNA extraction using the CTAB protocol [11]. The DNA extracted was used to amplify the partial region of the TEF1 gene by PCR and the PCR products were resolved by electrophoresis in 1.5% agarose gel, later purified with Promega's Wizard SV Gel and PCR Clean-Up System kit and they ordered sequencing to the Potosí Institute for Scientific and Technological Research (San Luis Potosí, Mexico).…”
Section: Molecular Characterization Of Fungal Isolatesmentioning
confidence: 99%
“…However, studies reporting phytopathogenic action of the fungi E. endophytica (Douanla-Meli & Scharnhorst, 2021), N. cubana (Li, Li, & Yang, 2021), and F. pseudocircinatum (Santillán-Mendoza et al, 2018;Kee, et al, 2020) were found.…”
Section: Fungi Identificationmentioning
confidence: 99%
“…De estos se eligieron con base en la obtención de bandas claras y su reproducibilidad en todos los ensayos, a los oligonucleótidos denominados UBC807, UBC811, UBC814, UBC825, UBC841, UBC842 y UBC844 (Cuadro 2), anteriormente utilizados en varios estu- dios (Lau et al, 2005;Li y Jin, 2008;Muthusamy et al, 2008;Datta et al, 2010;Gama-Maia y Torres, 2016;George et al, 2017). Las condiciones de amplificación siguieron el procedimiento realizado por Santillán-Mendoza et al (2018). Los productos de los amplicones se corrieron en geles de agarosa al 1.5%, con TBE 0.5×, a cinco voltios por centímetro (5 V/cm) y un marcador de peso molecular de 100 pb (New England Biolabs, UK).…”
Section: Muestreo De Materials Vegetalunclassified